Al →¹ Al₂O₃ →² Al₂(SO₄)₃ →³ Al(OH)₃
↓₄ ↓ ₅
Al₄C₃ AlCl₃
1) 4 Al + 3 O₂ → 2 Al₂O₃
↓
4) 4 Al + 3 C → Al4C₃
2) Al₂O₃ + 3 H₂SO₄ → Al₂(SO₄)₃ + 3 H₂O
↓
5) Al₂O₃ + 6 HCl → 2 AlCl₃ + 3 H₂O
3) Al₂(SO₄)₃ + 6 KOH → 3 K₂SO₄ + 2 Al(OH)₃
1) Zn + 2HCl = ZnCl2 + H2
Zn(0) + 2H(+) + 2Cl(-) = Zn(+2) + 2Cl(-) + H2(0)
Zn(0) + 2H(+) = Zn(+2) + H2(0)
2)Mg + ZnCl2 = MgCl2 + Zn
Mg(0) + Zn(+2) + 2Cl(-) = Mg(+2) + 2Cl(-) + Zn(0)
Mg(0) + Zn(+2) = Mg(+2) + Zn(0)
3) ZnO + 2NaOH + H2O = Na2[Zn(OH)4]
ZnO + 2Na(+) + 2OH(-) + H2O = 2Na(+) + Zn(OH)4 (-2)
ZnO + 2OH(-) + H2O = Zn(OH)4(-2)
4) реакции нет
5) NaOH + HCl = NaCL + H2O
Na(+) + OH(-) + H(+) + Cl(-) = Na(+) + Cl(-) + H2O
H(+) + OH(-) = H2O
6) 2NaOH + CuSO4 = Cu(OH)2 + Na2SO4
2Na(+) + 2OH(-) + Cu(+2) + SO4(-2) = Cu(OH)2 + 2Na(+) + SO4(-2)
2OH(-) + Cu(+2) = Cu(OH)2
7) 2NaOH + SO3 = Na2SO4 + H2O
2Na(+) + 2OH(-) + SO3 = 2Na(+) + SO4(-2) + H2O
2OH(-) + SO3 = SO4(-2) + H2O
1) 4Al+3O2=2Al2O3
2) Al2O3+3H2SO4=Al2(SO4)3+3H2O
3) Al2(SO4)3+6KOH=3K2SO4+2Al(OH)3
4) 4Al+3C=Al4C3
5) Al2O3+6HCl=2AlCl3+3H2O